High‐performance gas‐sensing properties of octahedral NiO crystals prepared via one‐step controllable synthesis route. Issue 2 (12th February 2014) - Lv, Yaohui; Huang, Kai; Zhang, Wei; Ran, Songlin; Chi, Fangli; Yang, Bin; Liu, Xianguo
<x xml:space="preserve">Abstract</x> Octahedrally shaped NiO particles with exposed 111 facets have been successfully synthesized through a one‐step composite‐hydroxide mediated route. The product was characterized by X‐ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM) techniques. Each octahedron is nearly perfect with a highly symmetric, regular shape containing 8 facets, 6 vertices, and 12 edges, which exhibits sharp edges and corners as well as smooth surfaces. The octahedral NiO particles display enhanced gas‐sensing properties in comparison with spherical‐like NiO particles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>